2014
DOI: 10.5897/ajfs2013.1099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on sensory characteristics and shelf-life of skimmed milk

Abstract: The present study was conducted to observe the effect of various heat treatments on sensory characteristics and shelf-life of skimmed milk at the Department of Animal Products Technology, Faculty of Animal Husbandry and Veterinary Sciences, Sindh Agriculture University Tandojam, during year 2012-2013. The skimmed milk was produced from buffalo milk through cream separator and then divided into four groups viz. A, B, C and D. The group A was kept as untreated (control) and B, C, D (treated at 60C for few s (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…While emissivity is denoted as ξ, the Stephen Boltzmann constant is denoted as δ, the space temperature is denoted as t s , and t e stands for exterior area temperature; it can be computed by using the following Equation (9).…”
Section: Calculation Of Thermodynamic Losses Of Steamingmentioning
confidence: 99%
See 1 more Smart Citation
“…While emissivity is denoted as ξ, the Stephen Boltzmann constant is denoted as δ, the space temperature is denoted as t s , and t e stands for exterior area temperature; it can be computed by using the following Equation (9).…”
Section: Calculation Of Thermodynamic Losses Of Steamingmentioning
confidence: 99%
“…Three of the nine solar thermal systems use flat plate collectors to preheat and clean hot water to meet 20 °C to 80 °C ranges of temperature. Essential points of the solar power system that have already been employed in the pasteurized plan to reach operating temperatures ranging from 63 °C to 72 °C include solar collectors, heat exchangers, and water heating systems [9]. Figure 2 represents the various reasons for selecting the solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate application of these tests allows product characterization and consumer preferences to be assessed (Drake, 2007). Many studies have investigated the impact of different heat treatments on the sensory properties of milk and dairy products (Jo et al, 2018;Li et al, 2018;Ul Haq et al, 2014;Zamberlin and Samaržija, 2017). Heat treatments can, for example, damage the flavor and/or texture of milk, as reported by Israr ul Haq et al (2014) on skimmed buffalo milk.…”
Section: Sensory Changesmentioning
confidence: 99%
“…Many studies have investigated the impact of different heat treatments on the sensory properties of milk and dairy products (Jo et al, 2018;Li et al, 2018;Ul Haq et al, 2014;Zamberlin and Samaržija, 2017). Heat treatments can, for example, damage the flavor and/or texture of milk, as reported by Israr ul Haq et al (2014) on skimmed buffalo milk. These authors reported that the appearance/color of pasteurized (65°C for 30 min) and sterilized milk (110°C for 10 min) was often considered nonacceptable compared to thermized skimmed milk (60°C for a few seconds) and raw milk.…”
Section: Sensory Changesmentioning
confidence: 99%
“…Thus, heat treatment of milk increased the RCT by 65% (Figure 1). Pasteurization induces the association of denatured whey proteins with the casein micelles, what result in deterioration of milk coagulation properties (Anema, 2008;Haq et al, 2014;.…”
Section: Effect Of Hp Treatment On Rennet Coagulation Time Of Milkmentioning
confidence: 99%